Media Pembelajaran Berbasis Android Pada Materi Fotografi Dasar - Nasruha, Muhammad Khalish; Akhyar, Ramaulvi Muhammad (TIN: Terapan Informatika Nusantara, 2025)
This research created an Android-based learning media product using the iSpring Suite to evaluate its feasibility before implementing it in the program's basic subjects for students in class X-DKV. The production of this learning media product categorizes research as a development study or R&D, using the 4D development paradigm. Data is collected through observation, interviews, and questionnaires, then analyzed using quantitative descriptive analysis. This study involved 2 media experts, 1 material expert, and 14 students of class X-DKV as product test subjects. Based on the results of the feasibility validation and trial of android-based learning media products by media experts, material experts and students, the results were very feasible. The average value of material feasibility validation is 54 more than 50.4 including the "Very Feasible" category. The average value of media feasibility validation is 51 more than 50.4 including the category "Very Feasible". The average value of the product trial was 56.6 more than 54.6 in the "Very Feasible" category. The overall average score of the feasibility test and product trial was 53.9 more than 51.8, so that this android-based learning media has a feasibility category of "Very Feasible". This research is sufficient on the feasibility of learning media only, for further research can be carried out on the effectiveness of Android-based learning media in the basic learning of the Photography Material Program, in addition to that the development of more varied learning media, both materials, and developer platforms used.